An acute fatality and post-mortem concentration distribution reveals a low potential for naproxen redistribution. Issue 4 (1st October 2016) - McIntyre, Iain M.; Valdez, Jose E.; Lucas, Jonathan R.
ABSTRACT: Therapeutic (or non-toxic) post-mortem naproxen blood and liver concentrations have not been previously described. Peripheral blood naproxen concentrations were compared with central blood and liver concentrations in 20 cases collected at autopsy from decedents determined to have taken therapeutic dosing of naproxen. Blood specimens were initially screened for alcohol and simple volatiles, drugs of abuse, alkaline, and acid/neutral drugs. Naproxen, when detected by the acid/neutral drug screen, was subsequently confirmed and quantified by a high performance liquid chromatography procedure. Overall, naproxen concentrations ranged from 0.19 to 33 mg/L in peripheral blood, 0.19 to 78 mg/L in central blood, and 0.23 to 86 mg/kg in liver. The median naproxen central blood to peripheral blood ratio was 1.4. Similarly, liver to peripheral blood ratios showed a median value of 1.0 L/kg. Also in this report, for the first time, naproxen concentrations are presented for a hospital admission blood (1, 040 mg/L), post-mortem peripheral blood, central blood, liver, and gastric contents in a case certified as death due to complications of acute naproxen intoxication. Given that a liver to peripheral blood ratio less than 5 L/kg is consistent with little to no propensity for post-mortem redistribution, these data suggest that naproxen shows a low propensity of redistribution.